Analysis of the Needs of Parents who Have Cerebral Palsy Children Reviewed from the Family Counseling - Nurhastuti, Nurhastuti; Kasiyati, Kasiyati; Zulmiyetri, Zulmiyetri; Iswari, Mega; Irdamurni, Irdamurni (Journal of ICSAR, 2020)
Parents who have children with cerebral palsy sometimes experience hopeless caring. Some parents feel shocked and cannot accept the fact that their child has a disability. Therefore we need an analysis of the needs of parents who have children with cerebral palsy. In the current study, to understand the needs of parents who have children with cerebral palsy, it is necessary to conduct family counseling in accordance with the cultural background and socio-economic level of the family. The purpose of this study is to explain the needs of parents who have children with cerebral palsy. This research is a quantitative study, namely research that uses explanatory research because this research was conducted in Padang, Indonesia, with a total sample of 13 parents who had children with cerebral palsy. The data source came from distributing questionnaires after family counseling was conducted to parents who had children with cerebral palsy. This study's results are that parental needs consist of several indicators, namely acceptance of parents who have children with cerebral palsy, factors that influence parents in receiving their children with cerebral palsy, and problems and obstacles faced by parents in dealing with their children with cerebral palsy.